Practical data communications for instrumentation and control - Park, John, 1953-; Mackay, Steve; Wright, Edwin, B.Sc. (Amsterdam ; London : Elsevier, 2003)
Instrumentation and control systems are highly reliant on data communications, so a working knowledge of the latest communications technologies and the essential protocols is essential for anyone designing, specifying or using instrumentation and control systems. This book is the only title on the market designed specifically for this audience. This is a comprehensive treatment of industrial data communication systems. Commencing with a thorough discussion of the popular RS-232, RS-422 and RS-485 standards it then moves on to industrial protocols, industrial networks and the communication requirements for the 'smart' instrumentation which is becoming de rigeur in industry today. The book also provides a solid grounding in the various Fieldbus and DeviceNet standards on the market today. This book provides you with the knowledge to analyse, specify and debug data communications systems in the instrumentation and control environment. *The essential guide to communications techologies and protocols for engineers designing, specifying or using instrumentation and control systems *Provides the knowledge required to analyze, specify and debug data communication systems, introducing the latest digital technologies *Coverage includes RS-232, RS422 and RS-485 standards, industrial networks and protocols, smart instrumentation, FieldBus and DeviceNet standards.
Overview of Data Communications; Basic Data Communication Principles; Physical Serial Communication Standards; Error Detection; Cabling Basics; Electrical Noise and Interference; Modems and Multiplexers; Introduction to Protocols; Open Systems Interconnection Model; Industrial Protocols; HART Protocol; Open Industrial Fieldbus and DeviceNet Systems; Local Area Networks; Appendix A: Numbering Systems; Appendix B: Cyclic Redundancy Check (CRC) Program Listing; Appendix C: Serial Link Design; Glossary.
Includes index.
Keywords: Automatic control; Data transmission systems; Electronic books